2017
DOI: 10.2147/ijn.s138400
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanoparticle-based miR155 antagonist macrophage delivery restores the cardiac function in ovariectomized diabetic mouse model

Abstract: Diabetic cardiomyopathy is a common disease in postmenopausal women, in whom the estrogen deficiency aggravates the pathology. In this study, we have found that estrogen deficiency due to ovariectomy aggravates the inflammation in the hearts of diabetic mice, as depicted by excessive proinflammatory type 1 macrophages (M1) over anti-inflammatory type 2 macrophages (M2). Accordingly, an additional increase of reactive oxygen species, cell apoptosis, cardiac hypertrophy, and fibrosis was observed in the hearts o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 45 publications
0
55
0
Order By: Relevance
“…A more recent study similarly reported alterations in streptozotocin-treated mouse hearts, including enhanced pro-inflammatory cytokine expression, fibrosis and decreased function that was associated with macrophage accumulation, but notably highlighted the negative impact of estrogen deficiency on these processes through the use of ovariectomized female mice ( Jia et al, 2017 ). These changes were also associated with increased expression of pro-M1/anti-M2 macrophage miR155.…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
“…A more recent study similarly reported alterations in streptozotocin-treated mouse hearts, including enhanced pro-inflammatory cytokine expression, fibrosis and decreased function that was associated with macrophage accumulation, but notably highlighted the negative impact of estrogen deficiency on these processes through the use of ovariectomized female mice ( Jia et al, 2017 ). These changes were also associated with increased expression of pro-M1/anti-M2 macrophage miR155.…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
“…Interestingly, in diabetic mice, miR‐155 is associated with macrophage‐mediated inflammation . miR‐155 is a potent promoter of M1 polarization, and it was found to be additionally enhanced in the macrophages.…”
Section: Targets Of Noncoding Rnas In Cardiovascular Disease With Diamentioning
confidence: 99%
“…miR‐155 is a potent promoter of M1 polarization, and it was found to be additionally enhanced in the macrophages. Cheng Ming Jia et al using gold nanoparticles (AuNPs) preferentially delivered antago‐miR‐155 to macrophages by phagocytosis. The results showed that miR‐155 was highly expressed in diabetic mice, and AuNP‐mediated cell‐specific inhibition of miR‐155 expression in macrophages promotes M2 polarization, represses inflammation, and thus restores the cardiac function.…”
Section: Targets Of Noncoding Rnas In Cardiovascular Disease With Diamentioning
confidence: 99%
See 1 more Smart Citation
“…Functional groups such as thiol and amino groups can be easily attached to the surface of AuNPs, and these chemically modified AuNPs have been employed as miRNA vehicles [62]. Jia et al reported the covalent conjugation of thiol-modified antagomir-miRNA-155 to AuNPs, and the administration of miRNA-155-AuNPs via tail vein injection promoted M2 macrophage polarization, reduced inflammatory mediators and ultimately recovered cardiac function in an ovariectomized (OVX) diabetic murine model [63].…”
Section: Lentiviral Vectorsmentioning
confidence: 99%